2020
DOI: 10.5430/ijfr.v11n4p74
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intellectual Capital on Firm Value: Empirical Evidence From Vietnam

Abstract: The paper aims to investigate the impact of intellectual capital on firm value in the context of Vietnam. The research sample includes 61 manufacturing companies listed on Vietnam stock market for the period from 2013 to 2018. Three statistical methods approaches are employed to address econometric issues and to improve the accuracy of the regression coefficients include Ordinary Least Square (OLS), Random Effects Model (REM) and Fixed Effects Model (FEM). This research uses value-added intellectual capital (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 22 publications
4
24
1
9
Order By: Relevance
“…[14], [15] show that companies with high levels of leverage will carry out extensive earnings management. [16] concluded that intellectual capital, human capital, and capital used did not affect firm value; furthermore, other researchers [17] showed that intellectual capital had a positive and significant effect.…”
Section: Introductionmentioning
confidence: 93%
“…[14], [15] show that companies with high levels of leverage will carry out extensive earnings management. [16] concluded that intellectual capital, human capital, and capital used did not affect firm value; furthermore, other researchers [17] showed that intellectual capital had a positive and significant effect.…”
Section: Introductionmentioning
confidence: 93%
“…The more unique resources that a company possesses, the greater its value. Nowadays, the traditional concept of value has been partially replaced by intellectual capital, which is often regarded as a competitive advantage (Sardo and Serrasqueiro 2017 ; Moon and Kym 2006 ; Setiany et al 2020 ; Ting et al 2020 ; Nguyen and Doan 2020 ; Salvi et al 2020 ).…”
Section: Literature Overviewmentioning
confidence: 99%
“…The capital employed efficiency is revealed using a ratio which discloses the extent to which the naira spent on using capital generates value for the company. Nguyen and Doan (2020); Ewereoke (2018); Kurfi, Noraza and Saleh (2017);and Onyekwelu, Okoh and Iyidiobi (2017) submitted that capital employed efficiency as a component of intellectual capital has a positive effect on firm performance. Okeke and Udeh (2020), assessed the effect of intellectual capital on the profitability of Nigerian deposit money banks.…”
Section: Effect Of Intellectual Capital Efficiency (Human Structural ...mentioning
confidence: 99%